Body representation disturbances in visual perception and affordance perception persist in eating disorder patients after completing treatment. Issue 1 (December 2017) - Engel, Manja; Keizer, Anouk
Abstract Body image disturbances (BID) are a key feature of eating disorders (ED). Clinical experience shows that BID exists in patients whoCompleted their Eating Disorder Treatment (CEDT), however studies concerning BID in CEDT patients are often limited to cognition and affect, measured by interviews and questionnaires. The current study is the first systematic study investigating the full scope of the mental body representation, including bodily attitudes, visual perception of body size, tactile perception, and affordance perception in CEDT patients. ED patients (N = 22), CEDT patients (N = 39) and healthy controls (HC;N = 30) were compared on BID tasks including the Body Attitude Test (BAT), Visual Size Estimation (VSE), Tactile Estimation Task (TET), and Hoop Task (HT). Results on the BAT show higher scores for ED patients compared to CEDT patients and HC but no difference between CEDT patients and HC. Both ED and CEDT patients show larger overestimations on the VSE and HT compared to HC, where ED patients show the largest overestimations. No group differences were found on the TET. The results indicate the existence of disturbances in visual perception and affordance perception in CEDT patients. Research focussing on more effective treatments for ED addressing multiple (sensory) modalities is advised.